PENSYARAHAN IBN ḤAJAR AL-‘ASQALĀNĪ TERHADAP KRITIK MATAN ‘ĀISYAH RA DALAM FATḤ AL-BĀRĪ - Muhammad Abu Nadlir (Wahana Islamika Jurnal Studi Keislaman, 2022)
‘Aisyah was one of the best sahabah who narrated hadis of the Prophet Pbuh. She also played a very large role in maintaining hadis of the Prophet Pbuh. very large. In fact, she did not hesitate to criticize hadis which he considered not in accordance with his intentions. However, it turns out the attitude of the salaf scholars in understanding this case varies. There are those who support the attitude of Āisyah and some who do not. This paper discusses the influence of matan critic of Āisyah Ra. to understanding Ibn Ḥajar al-‘Asqalānī in book under title Fatḥ Al-Bārī. To find how Ibn Ḥajar Al-‘Asqalānī's method of devotion to matan Āisyah Ra. in the book under title Fatḥ Al-Bārī and how the influence of matan critic of ‘Āisyah Ra. to the sacrifice of Ibn Ḥajar Al-‘Asqalānī in the Fatḥ Al-Bārī. This research is a library research. The sources’s data are primary sources, namely al-Ijābah li 'īrādi mā Istadrakathu ‘Āisyah‘ alā aṣ-Ṣahābah by Badruddin az-Zarkasyi and Fatḥ Al-Bārī by Ibn Ḥajar; and secondary sources is scientific books that are of relevance to Ibn Ḥajar Al-‘Asqalānī's book in the Fatḥ Al-Bārī and critics of matan ‘Āisyah. Based on the results of the study, it was found that; Ibn Ḥajar Al-‘Asqalānī's method of devotion to matan atan Āisyah Ra. in Fatḥ Al-Bārī is the method of al-Jam'u wa at-Taufiq, and at-tarjih. It was found also that it turns out that the critique of Āisyah did not always affect Ibn Ḥajar al-‘Asqalānī's devotion. It was proven that there was criticism ‘Aisyah who was not considered and there was also a compromise with the criticized.